Exploitation of trust in instant messaging : a case study on online chats. - Mohamed Saifulamri Omar. (2010)
Today, the Internet has revolutionized the way we live. It is shaping the way we communicate and socialize. For instance, online chats through instant messaging software provided real-time communications across physical boundaries. Most of these software are freely available. However, there are dangers in chatting online. We read of reports on cyber predators, People who stalk children and young adults in the Internet and expose them to pornography, always lurk behind online chats to on unsuspecting victims. They employ social engineering techniques, that is, forming belief in young adults to gain trust. They do so by gathering information about young adults, developing relationships to build trust and later exploiting that trust to execute sexual abuses.